(untitled) (Journal of Fiber Bioengineering and Informatics, 2019)
In this study, the wool-based activated carbon tubes (ACTs) were successfully prepared by potassii as additive. The ACTs had formed a tubular morphology with numerous pores located in both two sides. The mechanism of the tube formation were mainly investigated by removing overlapping scales on the surface of fibers and comparing the effects of experimental parameters. The removal method were carried out by formic acid and ultrasonic wave oscillation. The influence between scales and tubes was characterized by scanning electron microscopy (SEM), thermogravimetric analysis (TGA), methylene blue (MB) through discussing the morphology study, thermal property and adsorption capacity of ACTs. The surface morphology of the ACTs were affected by carbonization temperature, while the scale layers has no relations with the formation of a tubular morphology. Scale layers had almost no effects on thermal decomposition because close weight loss between ACKC2 and ACKC5. The adsorption capacity of ACTs from raw wool using two-step method is in the range of 18.50-26.75 mg/g, which was obviously higher than using one-step method with 14.40-84.00 mg/g. The adsorption capacity of ACTs decreased because of the removal of scale layers using one-step, which is contrary to ones using two-step.